1994
DOI: 10.1128/mcb.14.10.6936
|View full text |Cite
|
Sign up to set email alerts
|

Deletion and replacement of the mouse adult beta-globin genes by a "plug and socket" repeated targeting strategy.

Abstract: We describe a two-step strategy to alter any mouse locus repeatedly and efficiently by direct positive selection. Using conventional targeting for the first step, a functional neo gene and a nonfunctional HPRT minigene (the "socket") are introduced into the genome of HPRT-embryonic stem (ES) cells close to the chosen locus, in this case the j8-globin locus. For the second step, a targeting construct (the "plug") that recombines homologously with the integrated socket and supplies the remaining portion of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Several methods for the introduction of mutations in the mouse genome have been described (3,19,23,25,55,58,59). Despite the potential advantages, relatively few studies have used these approaches to determine the role of cis-acting sequences (7,20,37,50,57).…”
mentioning
confidence: 99%
“…Several methods for the introduction of mutations in the mouse genome have been described (3,19,23,25,55,58,59). Despite the potential advantages, relatively few studies have used these approaches to determine the role of cis-acting sequences (7,20,37,50,57).…”
mentioning
confidence: 99%
“…1). To facilitate recovery of the targeted clones, we combined to this scheme the plug-and-socket strategy developed by Detloff et al (11), which is based on the restoration by homologous recombination of a functional Hygro r gene. Introduction of the I-SceI recognition site into the endogenous villin locus.…”
Section: Resultsmentioning
confidence: 99%
“…To alleviate the screening of recombined clones during the second step, we used a strategy similar to the plug-and-socket strategy previously described by Detloff et al (11). They reported that using linearized constructs, insertion (O-type) targeting events occurred in their experiment, noticeably reducing the proportion of desired replacement recombinational (⍀-type) events among the drug-resistant clones.…”
Section: Discussionmentioning
confidence: 99%
“…The 'tag and exchange' strategy involves also two sequential gene targeting steps using two different replacement type vectors (Askew et al 1993). A modification of this protocol is the so-called 'plug and socket' approach developed by Detloff et al (1994). A much simpler method for introducing subtle mutations into the target gene has been developed by Reid et al (1991) and Davis et al (1992).…”
Section: Introduction Of Subtle Mutationsmentioning
confidence: 99%